Modeling and Monthly Price Forecasting of Steel in Iran - Tayyebeh Rahnemoon Piruj; Seyed Saleh Akbar Mousavi; Mansour Asgari (اقتصاد باثبات, 2024)
The abundant and numerous uses of steel in various industries have turned it into a strategic commodity, and its price has always been a concern of industrial owners. Therefore, access to accurate forecasts of the price trend of steel and its products is important. Therefore, in the present study, while identifying the determinant variables for the price of steel, an out-of-sample forecast for 2023:10 to 2024:06 has been made using the vector autoregression (VAR) model. At first, the results of the Johansen-Juselius cointegration test confirmed the long-term relationship. Also, the error correction coefficient (ECM) was -0.0842. We analyze impulse response functions. The unofficial exchange rate, and industrial producer price index (base metal manufacturing sub-group) (respectively with a positive effect of 6.8% and 6.5% percent in the standard form) have been more effective than other model variables on the fluctuations of steel price. In addition, the results of variance decomposition showed that the industrial producer price index (16.18%), and unofficial exchange rate (11.7%) after the price of steel itself had more effect on the price fluctuations of this product than other variables. Finally, we estimate the out-of-sample forecast. The price of steel is forecasted from 302,445 Rials in October 2023 to 321,552 Rials in June 2024 (with a 5% increase). Based on the forecast evaluation criteria, our model can accurately forecast the price trend of steel. According to the results, the most important policy recommendations include updating the technologies, equipment, and machinery used in the production of steel products to develop the production of steel products, saving energy consumption and production costs, adopting appropriate monetary and foreign exchange policies, And increasing exports by focusing on marketing and sales of steel products (to prevent raw sales), through the development of production, increasing the variety, quality, and durability of manufactured steel products can be provided